Political sociology - the state of the art - Mitra, Subrata Kumar; Pehl, Malte; Spieß, Clemens (Verlag Barbara Budrich, 2010)
The World of Political Science - New volumes The book traces the disciplinary development of political sociology and the transdisciplinary research into the overlapping issues involving politics and society. The contributions cover overviews of the history, methodological and theoretical development of this academic discipline. Successes as well as failures in past, unexplored areas and salient issues in ongoing research are also highlighted. From the Contents: Subrata K. Mitra and Malte Pehl, Taking Stock of Political Sociology Dirk Berg-Schlosser, Political Culture at a Crossroads? Kay Lawson and Mildred Schwartz, Parties, Interest Groups and Social Movements: Shall Change be Mid - wife to Truth? Eva Etzioni-Halevy, Socio-Political Inequalities: Elites, Classes and Democracy Prakash Sarangi, Contemporary Approaches to the Study of the State Jan van Deth, Political Sociology: Old Concerns and New Directions
Keywords: Konferenzschrift -- 2005 -- Heidelberg; Aufsatzsammlung; Politische Soziologie